The Pediatric Guideline Adherence and Outcomes (PEGASUS) programme in severe traumatic brain injury: a single-centre hybrid implementation and effectiveness study. (January 2019) - Vavilala, Monica S; King, Mary A; Yang, Jen-Ting; Erickson, Scott L; Mills, Brianna; Grant, Rosemary M; Blayney, Carolyn; Qiu, Qian; Chesnut, Randall M; Jaffe, Kenneth M; Weiner, Bryan J; Johnston, Brian D
Summary: Background: As far as we know, there are no tested in-hospital care programmes for paediatric traumatic brain injury. We aimed to assess implementation and effectiveness of the Pediatric Guideline Adherence and Outcomes (PEGASUS) programme in children with severe traumatic brain injury. Methods: We did a prospective hybrid implementation and effectiveness study at the Harborview Medical Center (Seattle, WA, USA). We included children (aged <18 years) with traumatic brain injury (trauma mechanism and image findings). We assessed service provision, adherence to three key performance indicators, and discharge outcomes associated with the PEGASUS programme. The three key performance indicators were early initiation of enteral (oral or tube feeds) or parenteral nutrition; avoidance of any unwanted hypocarbia (PaCO2 <30 mm Hg) without brain herniation; and maintenance of cerebral perfusion pressure (>40 mm Hg) for 72 h after the diagnosis of severe traumatic brain injury. Poisson regression with robust standard errors was used to estimate the association between adhering to key performance indicators and discharge outcomes. Findings: Between May 1, 2011, and July 1, 2017, 199 children (median age 11·9 years [IQR 3·4–16·1]) participated in the PEGASUS programme, of whom 193 (97%) had severe traumatic brain injury and six (3%) had moderate traumatic brain injury. 105 patients contributed data for all three key performance indicators. Adherence to at least one key performance indicator was achieved by 101 (96%) of 105 participants, and 44 (42%) achieved adherence to all three key performance indicators. Programme participants achieved adherence to the key performance indicators of hypocarbia (76 of 105 [72%]), nutrition (162 of 199 [81%]), and cerebral perfusion pressure (128 of 199 [64%]). Adherence to the nutrition key performance indicator was associated with higher discharge survival (relative risk [RR] 2·70, 95% CI 1·54–4·73) and a more favourable discharge disposition (3·05, 1·52–6·11). Adherence to the cerebral perfusion pressure key performance indicator was also associated with higher discharge survival (RR 1·33, 95% CI 1·12–1·59) and favourable disposition (1·53, 1·19–1·96). Adherence to each additional key performance indicator was associated with higher survival (RR 1·27, 1·12–1·44) and a more favourable discharge disposition (1·46, 1·23–1·72), in a dose-response manner. Interpretation: The multilevel, hospital-wide, high-fidelity PEGASUS programme might benefit children and adolescents admitted to the emergency department with severe traumatic brain injury. Cerebral perfusion pressure, nutrition, and hypocarbia targets are essential components of the PEGASUS programme and are associated with favourable discharge outcomes. Funding: National Institutes of Health.